Mechanistic Study of Oxidation of Benzyl Ethers by 1-Chlorobenzotriazole in Glacial Acetic Acid - Mathiyalagan, N.; Priya, V. (Asian Journal of Chemistry, 2010)
In present studies, the kinetics of oxidation of benzyl ethers by 1-chlorobenzotriazole (CBT) in the presence of HClO4 in aqueous acetic acid medium is reported. The observed rate of oxidation is first order with respect to [CBT] and [H+]. The order with respect to [benzyl ether] is zero. The rate of the reaction increases with increase in the dielectric constant of the medium. Addition of benzotriazole has negligible effect on the rate of oxidation. The major product of oxidation is benzaldehyde. Arrhenius and activation parameters have been calculated. A suitable mechanism has been proposed and a rate law explaining the experimental results is derived.